Vertical Integration and Zero-Rating Interplay: An Economic Analysis of Ad-Supported and Ad-Free Digital Content. Issue 4 (1st October 2020) - Cho, Soohyun; Qiu, Liangfei; Bandyopadhyay, Subhajyoti
ABSTRACT: We discuss the economic impacts of the interplay between vertical integration and zero-rating for digital content. To this end, we develop a game-theoretic model that involves an Internet Service Provider (ISP), two competing content providers (CPs)—one an ad-supported CP, the other ad-free—and consumers. While previous studies have separately examined vertical integration and zero-rated content, none to our knowledge has explored the simultaneous interaction of both phenomena, which became apparent after the historic merger of AT&T and Time Warner. This vertical integration of an ISP and a CP has sparked an intense debate among policymakers and practitioners alike over the economic implications and consequent business practices (e.g., zero-rated content). The results of our analysis show that an ISP can generate higher profits after the merger with zero-rated content. Surprisingly, we find that the consumer valuation of the ad-free content significantly affects how the ISP will decide to maximize its profit. We extend our model to additionally consider the CPs' partial sponsorship of their consumers' data usage as well as the ISP's different pricing schemes for its consumers and the CPs. Our analysis, which illustrates the various arrangements between vertical integration and zero-rated content, and our findings on consumer surplus and social welfare should be helpful to policymakers as well as to the ISPs, CPs, and consumers of digital content.